Intertwined Signaling Pathways Governing Tooth Development: A Give-and-Take Between Canonical Wnt and Shh - Hermans, Florian; Hemeryck, Lara; Lambrichts, Ivo; Bronckaers, Annelies; Vankelecom, Hugo (Frontiers in Cell and Developmental Biology, 2021)
Teeth play essential roles in life. Their development relies on reciprocal interactions between the ectoderm-derived dental epithelium and the underlying neural crest-originated mesenchyme. This odontogenic process serves as a prototype model for the development of ectodermal appendages. In the mouse, developing teeth go through distinct morphological phases that are tightly controlled by epithelial signaling centers. Crucial molecular regulators of odontogenesis include the evolutionarily conserved Wnt, BMP, FGF and Shh pathways. These signaling modules do not act on their own, but are closely intertwined during tooth development, thereby outlining the path to be taken by specific cell populations including the resident dental stem cells. Recently, pivotal Wnt-Shh interaction and feedback loops have been uncovered during odontogenesis, showing conservation in other developing ectodermal appendages. This review provides an integrated overview of the interplay between canonical Wnt and Shh throughout mouse tooth formation stages, extending from the initiation of dental placodes to the fully formed adult tooth.